Ash'arism encounters Avicennism: Sayf al-Dīn al-Āmidī on creation - Hassan, Laura ca. 20.Jh. - (Islamic history and thought, 2020)
"This study of Sayf al-Dīn al-Āmidī's (d. 631/1233) teachings on creation offers close analysis of all of his extant works of falsafa and kalām. Some of these were not known to previous scholars, yet they bear witness to key facets of the interaction between the historically inimical traditions of Hellenic philosophy and rational theology at this important intellectual moment. Al-Āmidīis seen to grapple with the encounter of two paradigms for the discussion of creation. On the one hand, Ibn Sīnā's metaphysical concept of necessity of existence is the basis of his doctrine of the world's pre-eternal emanation. On the other, for the mutakallimūn, the physical theory of atomism bolsters the view that God created the world from nothing. This study is of interest to scholars of Ibn Sīnā and Ash'arism alike, as it advances our understanding of the ongoing tradition of rational theology in the Islamic world, long past Abū Ḥāmid al-Ghazālī's (d. 505/1111) famous attack on the philosophers"--